ANTIFUNGAL ACTIVITIES OF ETHANOL EXTRACT OF ROSEMARY LEAF (Rosemarinus officinalis L.) AGAINST Candida albicans - Swari, Dewa Ayu Made Adnya; Santika, I Wayan Martadi; Aman, I Gusti Made (Journal Pharmaceutical Science and Application, 2020)
Background: This study was a preliminary study aimed to investigating the in vitro activity of rosmarinic acid contained on Rosemary leaves ( Rosemarinus officinalis L. ) on the Candida albicans . Rosmarinic acid can be an inhibitor of the RTPase enzyme in the fungus Candida albicans . Objective: This study is expected to provide information in the development of science about the antifungal activity of ethanol extract of Rosemary leave (Rosmarinus officinalis L.) againsts C.albicans. The recent research was an laboratory experimental. Experiments on an ethanol extract of Rosemary leaves ( Rosemarinus officinalis L. ) and post-test design of the control group. Methods: The extraction method used in this study was a multilevel extraction method. The antifungal activity testing method uses discs and MIC methods. Replication was done six times at two concentration namely, 80% (b/v) and 100% for each measurement. R esults : The data analysis was carried out using SPSS with 95% of confidence level with the Kruskal Wallis analysis then completed with the Mann Whitney U test. The results of the MIC experiment showed all the various concentrations of ethanol extract performed Candida albicans growth on the surface of the media. Extract with 80% (b/v) concentration showed greater antifungal activity. Furthermore the MIC was shown by 80% (b/v) concentration of the ethanol extract of Rosemary leaves against Candida albicans . The test results of the antifungal activity of the Rosemary leaf ethanol extract showed the presence of inhibitory diameter in the ethanol extract of the Rosemary leaf concentration of 80% (b/v) with a mean ± SD of 10.6 ± 0.57735 and RSD of 5.774%. Conclusion: The ethanol extract of Rosemary leaves (Rosmarinus officinalis L.) has an inhibitory effect on the fungus Candida albicans at a concentration of 80% (b / v) Keywords: Antifungal activity, Candida albicans , Rosemary, RTPase, ethanol extract